The Importance of Pedagogical Subjects in Forming Innovative Pedagogical Activity in Future Teachers - Djalolova Sevara Kholmurodovna (Genius Journals, 2022)
Pedagogy cannot achieve perfection alone. He, like other sciences, uses the achievements of social science and regularly interacts with other sciences. As a result of upbringing and training, certain personality qualities are formed in a person. Through upbringing and training, a person acquires spiritual and intellectual qualities that he did not have before. This state continues continuously throughout the life of the individual and becomes a factor in his development. Pedagogy as a science of Man and its formation is inextricably linked with philosophy, ethics, aesthetics, Cultural Studies, Psychology, Economics, Political Science, demography, history, literature, medicine, mathematics and other science
Keywords: Correctional; Surdopedagogy; Oligophrenopedagogy; oligophrenopsychology